(untitled) (Journal of the College of Education for Women, 2019)
The research addressed an analytical field investigation of the locality of meander, the factors responsible of the locality of the meander at certain points of the stream other than others, and the role sequence of these factors in the formation process.The research revealed that the location of forming the meander was associated closely with the scale structural composition of the bank materials from which the first stage of forming the curved stream, for the inhomogeneous or non-identical opposite banks in their scale structural composition saw an activity of differential corrosion, while the homogeneous and identical opposite banks in their scale structural composition saw an identical corrosion activity in its intensity at both banks. The research investigated in field the presence of scale variation of the materials of opposite banks in the location of forming the meander which was not found at the incurved stream banks by taking samples and analyze them in scale. The analysis results showed that the synclinal bank was with high sand ratio which was the reason behind the activity of corrosion process due to its weak cohesion, high permeability, and highroughness creating an environment of frequent turmoil reverse eddy currents. As to its opposite bank which represented the convex bank, the results of the scale analysis showed its soil to be with high content of mud; therefore, it was resistant to the corrosion activity compared to the synclinal bank, being more cohesive and of weak permeability, it was soft, so it did not create a turmoil eddy motional environment of the aquatic currents. While in the incurved stream, the results of the scale analysis showed that the soil of both opposite banks were identical in its volume content; therefore, the activity of the corrosion process was identical at both banks and its high sand ratio resulted in the expansion of the stream and not its fold.The research revealed that the circularity of the curved stream imposed the presence of the centrifugal force which appeared in the domains of the circular motion, changing the concentration locations of the currents. As it is well-known, the fastest currents in the river are those which locate far away from the bottom and the banks, and are found in the middle of the stream which we really found in the incurved stream, but due to the control of the centrifugal force, we found that the fastest currents were concentrated at the synclinal banks and that the slowest currents were concentrated at the synclinal banks, which explains logically and realistically due to the contrast of the corrosion and sediment activity in the curved river streams and the presence of centrifugal force was responsible of the development of these streams from fold to curve to turn to cut lake.The research defined the morphology of the curved stream at any stage of the development stages at the presence of three corrosion units that represent the synclinal banks meeting three sedimentary units represent the convex banks, two of which were opposite to each other represent overall the neck of the stream and the stream in its complete shape was represented by the overall of these corners